Effect of Storage on the Quality of Sachet Water Consumed by Households in Nsukka Zone - P.B., Mberekpe; N. M, Eze (Journal of Home Economics Research, 2024)
The purpose of this study was to investigate the effect of storage on the quality of sachet water consumed by households in Nsukka zone of Enugu State. Two Research Questions guided the study. Experimental design was used. Four brands of sachet water were randomly selected by balloting from seventeen brands of sachet water identified in the zone. The duration and storage environment included day one as the control, 2 weeks, 5 weeks and 8 weeks and refrigeration and outdoor storage environment. The sensory and microbial evaluations were conducted using 9- point hedonic rating scale and multiple number counts (MPN). The findings indicated that all brands of sachet water had E.coli at day one. Refrigerated water had the best taste and odour at 2 weeks and very minute microbial content at 8week of storage. It was recommended that, for the safety of sachet water consumers, the storage duration should not exceed fourteen (14) days of production.